Profil Primigravida Muda dan Luaran Persalinan di Rumah Sakit Dr.Oen Surakarta - Supanji Raharja; Ova Emilia; Poedji Rochjati (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: Pregnancy at a young age has become an important health problem both in developed and developing countries. Pregnancy at a young age increases the risk of maternal and perinatal morbidity and mortality. This is because adolescent women who are not ready both physically and psychologically to get pregnant.Obsjective: This study aims to identify and analyze labor in young primigravida (<20 years) with pathological labor in hospital Dr.Oen Surakarta.Method: This was an observational analytic study without intervention in the form of comparative cross sectional study conducted in young primigravida group age <20 years and primigravida group age 20 to 34 years old, who underwent labor in hospital delivery room. Dr.Oen Surakarta. This study used secondary data from the medical record of pregnant women who gave birth at RS.Dr.Oen Surakarta from January 1, 2011 to December 31, 201. A comparison between young primigravids (<20 years) in which pathologic pathways were performed with primigravida of reproductive age (20-34 years) experienced pathological labor were conducted.Result and Discussion: The number of deliveries in young primigravida (<20 years) was 61 people (6.65%) whereas in primigravida (21-35 years) there were 856 people (93.34%). Younger primigravids have lower levels of education than the primigravida age of reproductive age (p 0.00, CI 3.557 - 11.227). The younger primigravida has a tendency to give birth outside its residence area compared to primigravida of reproductive age (p 0.00; CI 0.050,178). Unmarried status in the young primigravida is greater than that of primigravida of reproductive age (p 0.00, CI 0.011 - 0,229) .An Antenatal Care on Primigravida reproductive age is more regular than young primigravida (p 0.03; CI 0.255 - 0.97) . Young primigravida tended to have anemia (p = 0.00, OR 8.4 CI 3.22 - 21.93) The risk of prematurity was higher in young primigravids than in the reproductive age primigravida (p 0.01, OR 2.9 CI 1, 16 - 7.25). Younger primigravids have a higher risk for pathologic delivery compared to primigravida of reproductive age (p 0.05 OR 0.56 CI 0.315 - 1.01).Conclusions: There are differences in terms, level of education, marital status, residence, regularity of ANC between young primigravida and prmigravida of reproductive age. The study found that young primigravids have a higher risk of occurrence of anemia, prematurity and pathologic delivery compared with healthy reproductive age primigravids.Keywords: young primigravida, primigravida healthy reproductive age, risk factors